Hydroxyapatite - Advances in Composite Nanomaterials, Biomedical Applications and Its Technological Facets 2018
DOI: 10.5772/intechopen.71489
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Calcium Phosphates Derived from Marine and Land Bioresources

Abstract: This chapter aims to establish the key factors for technological optimization of biogenic calcium phosphate synthesis from marine and land resources. Three natural calcium sources-marble, seashell and bovine bone-were considered as raw materials. The proposed materials are suitable candidates for the synthesis of bone substitutes similar to the inorganic bone component. The synthesis processes were developed based on the investigations of thermal phenomena (TGA-DSC analysis) that can occur during thermal treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…In 2018, 5.8, 1.6, and 0.4 million tons of oyster, mussel, and cockle were produced, respectively [ 2 ]. Generally, bivalve shell wastes account for about 65–80% of live weight, which is expected to be over 5 million tons a year [ 4 ]. Large numbers of bivalve shells are dumped into public waters and/or landfills and create numerous environmental obstacles that contribute to pollution to coastal fisheries, public water surface, an unpleasant smell as a consequence of the decomposition of organics attached to the shells, and natural landscape affecting to health/sanitation problems [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, 5.8, 1.6, and 0.4 million tons of oyster, mussel, and cockle were produced, respectively [ 2 ]. Generally, bivalve shell wastes account for about 65–80% of live weight, which is expected to be over 5 million tons a year [ 4 ]. Large numbers of bivalve shells are dumped into public waters and/or landfills and create numerous environmental obstacles that contribute to pollution to coastal fisheries, public water surface, an unpleasant smell as a consequence of the decomposition of organics attached to the shells, and natural landscape affecting to health/sanitation problems [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, bivalve shell wastes account for about 65–80% of live weight, which is expected to be over 5 million tons a year [ 4 ]. Large numbers of bivalve shells are dumped into public waters and/or landfills and create numerous environmental obstacles that contribute to pollution to coastal fisheries, public water surface, an unpleasant smell as a consequence of the decomposition of organics attached to the shells, and natural landscape affecting to health/sanitation problems [ 2 , 3 , 4 , 5 ]. Consequently, the disposal of bivalve shell wastes is getting an extremely fatal issue for the marine aquaculture industries and various consumer countries.…”
Section: Introductionmentioning
confidence: 99%
“…The main sources are generally from aquaculture rather than wild fisheries, among which oysters are dominant followed by mussels and cockles. In 2018, 5.8, 1.6, and 0.4 million tons of oyster, Realizing this problem, our research focuses on the conversion of bivalve shells to calcium phosphates, which are used as nutritional supplements, catalysts for some chemical reactions, fertilizers and animal feed minerals, mineral basis of the tooth and bone tissues as well as for creating materials with unique properties [1,[4][5][6][7][8][9]. In Thailand, monocalcium phosphate (MCP) and tricalcium phosphate (TCP) are enormously used in many fields and both compounds are imported every year.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium carbonate (CaCO 3 ) emerged as a sustainable bioresource for various calcium phosphates synthesis along with coralline hydroxyapatite [ 1 ] and soon became a target subject for the extensive research in the reconstructive orthopedics field. Now both the marine (corals, seashells, cockleshells, cuttlefish bones) and terrestrial forms (marble, land snails) of CaCO 3 are known as an eco-friendly, sustainable and geographically available resource, but improvements are still necessary in terms of calcium phosphates synthesis parameters [ 2 ]. The use of natural materials and structures for medical purposes was motivated by the limitations of synthetic materials generation in regard to the necessary mechanical features and integrity [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural materials and structures for medical purposes was motivated by the limitations of synthetic materials generation in regard to the necessary mechanical features and integrity [ 3 , 4 , 5 , 6 ]. In terms of targeted precursors, dolomitic marble and Mytilus galloprovincialis seashells, autochthonously available, represent two different calcium carbonate polymorphic forms—calcite and aragonite—which have similar chemical composition, except for the Mg ion content that defines the dolomitic marble species [ 2 ]. Research carried out has shown that both marine and terrestrial resources can be an appropriate resource for biological phase-pure and thermally stable CPC (calcium phosphate ceramics) production [ 7 ].…”
Section: Introductionmentioning
confidence: 99%